Odpowiedzi

2013-08-14T06:34:37+02:00
C)
8x - 0,2 = 8x - 0,1
8x - 8x = 0,2 - 0,1
0 = 0,1
równanie sprzeczne

d)
0,01x+17 = -0,16x
0,01x + 0,16x = -17
0,17x = -17 /: 0,17
x = -100

e)
-0,07(10x - 1) = 0,3x
-0,7x + 0,07 = 0,3x
-0,7x - 0,3x = -0,07
-x = -0,07 /:(-1)
x = 0,07

f)
0,83x + 0,82 = 0,23x + 1,52
0,83x - 0,23x = 1,52 - 0,82
0,6x = 0,7 /:0,6
x = 7/6

g)
0,6x + 2(0,1x - 0,1) = 0,2(x + 1)
0,6x + 0,2x - 0,2 = 0,2x + 0,2
0,8x - 0,2x = 0,2 + 0,2
0,6x = 0,4  /:0,6
x = 2/3

h)
0,7(x + 4) = 0,4(x + 1) + 0,3x + 1
0,7x + 2,8 = 0,4x + 0,4 + 0,3x + 1
0,7x + 2,8 = 0,7x + 1,4
0,7x - 0,7x = 1,4 - 2,8
0 = -1,4
równanie sprzeczne

i)
0,15(2x + 4) = 2(1,3 + 0,3x) - 0,6
0,3x + 0,6 = 2,6 + 0,6x - 0,6
0,3x - 0,6x = 2 - 0,6
-0,3x = 1,4  /:(-0,3)
x = -14/3

1 5 1